History of science, philosophy, and culture in Indian civilization.he state and society in medieval India - Grewal, J. S. (New Delhi : PHISPC ; Oxford University Press, 2005)
Contributed research papers.
Includes bibliographical references and index.
Keywords: India -- Politics and government; India -- Social conditions